Resilient reporting : Media coverage of Irish elections since 1969 - Breen, Michael (Manchester University Press, 2019)
This book examines how election news reporting has changed over the last half century in Ireland by means of a unique dataset involving 25m words from newspapers as well as radio and television coverage. The authors examine reporting in terms of framing, tone, and the distribution of coverage. They also focus on how the economy has affected election coverage as well as media reporting of leaders and personalities, gender and the effect of the commercial basis of media outlets. The finding - drawn from a machine learning computer system involving a huge content analysis study - will interest academics as well as politicians and policy makers internationally.